Highly conductive and heat-resistant cable material for new energy vehicles and preparation method thereof
By adding a specific proportion of oxides to copper and using high-temperature melting treatment and inert gas boosting technology, a high-conductive heat-resistant cable material is formed, which solves the problem of copper alloy rising resistance at high temperatures and achieves high efficiency of new energy vehicles Prolonged conductivity and battery life.
Patent Information
- Application Number
- CN202410793323.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-06-19
AI Technical Summary
The resistance of existing copper alloy materials has significantly increased at high temperatures, making it difficult to meet the conductive performance needs of new energy vehicles, resulting in increased energy loss and shortened battery life.
Infused with specific ratios of bismuth trioxide, boron trioxide, tellurium trioxide, and antimony trioxide in copper, and through high-temperature melting treatment and inert gas boosting technology, a highly conductive and heat-resistant cable material is formed to ensure that it is in high temperatures The resistance is less improved and the conductivity is better than that of pure copper.
It realizes maintaining low resistance at high temperatures, reducing energy losses, and extending the battery life of new energy vehicles, and the material's conductive performance is close to pure copper at low temperatures.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of cable materials, and in particular to a high-conductivity and heat-resistant cable material for new energy vehicles and a preparation method thereof. Background Art
[0002] Wires and cables are wire products used to transmit electrical energy, mainly including conductors and insulation layers. Wires are materials used for conducting electricity. The lower the resistance of the wire, the higher the conductivity, the higher the efficiency of transmitting electrical energy, and the better it can reduce energy loss during the transportation of electrical energy. Copper is often used as the main material for conductors due to its lower resistance.
[0003] Although copper has a low resistance, at high temperatures, its resistance will increase significantly as the temperature rises, resulting in greater losses when the cable transmits electrical energy in a high-temperature environment, greatly reducing energy utilization. When used in new energy vehicles, reducing energy loss is the key to extending battery life. Therefore, cable materials that can maintain low resistance at high temperatures are needed to make cables. Although other raw materials are added to copper to make alloy materials in the prior art, the resistance of such alloy materials at high temperatures is still high, which makes it difficult to meet the needs of new energy vehicles. Therefore, there is still room for improvement. Summary of the invention
[0004] In order to improve the electrical conductivity of cable materials at high temperatures, the present application provides a high-conductivity and heat-resistant cable material for new energy vehicles and a preparation method thereof.
[0005] In the first aspect, the present application provides a high-conductivity and heat-resistant cable material for new energy vehicles, which adopts the following technical solution: a high-conductivity and heat-resistant cable material for new energy vehicles, which is made of the following components in parts by mass:
[0006] Copper 80-84 parts;
[0007] 6-7 parts of bismuth trioxide;
[0008] Boron trioxide 2-3 parts;
[0009] Tellurium oxide 5-6 parts;
[0010] 3-4 parts of antimony trioxide.
[0011] By adopting the above technical scheme, by adding bismuth trioxide, boron trioxide, tellurium oxide and antimony trioxide into copper in a specific proportion, the obtained new energy vehicle high conductivity heat-resistant cable material has less resistance increase at high temperature, has good high temperature resistance, and can maintain high conductivity. At low temperatures, the conductivity is close to that of pure copper materials, and at high temperatures, the conductivity is better than that of pure copper materials. It is very suitable for use in new energy vehicles.
[0012] Preferably, the mass ratio of copper, bismuth trioxide, boron trioxide, tellurium oxide and antimony trioxide is 82:6.5:2.5:5.5:3.5.
[0013] By adopting the above technical scheme and specifically selecting the mass ratios of copper, bismuth trioxide, boron trioxide, tellurium oxide and antimony trioxide, the obtained high-conductivity and heat-resistant cable material for new energy vehicles has less resistance increase at high temperatures, better conductivity at high temperatures, better reduction of energy loss, and is more conducive to extending the battery life when used in new energy vehicles.
[0014] In the second aspect, the present application provides a method for preparing a high-conductivity and heat-resistant cable material for new energy vehicles, using the following technical solution:
[0015] A method for preparing the above-mentioned high-conductivity and heat-resistant cable material for new energy vehicles comprises the following steps:
[0016] Step 1), copper, bismuth trioxide, boron trioxide, tellurium oxide, and antimony trioxide are uniformly mixed to obtain a mixed material;
[0017] Step 2), heating the mixed material to 1130-1150° C., maintaining the temperature at 1130-1150° C. for 60-70 minutes, to obtain a composite metal liquid;
[0018] Step 3), injecting the composite metal liquid into the mold and cooling it to form a high-conductivity and heat-resistant cable material for new energy vehicles.
[0019] By adopting the above technical solution, by maintaining a constant temperature of 1130-1150℃ for 60-70min, copper, bismuth trioxide, boron trioxide, tellurium oxide and antimony trioxide can be better mixed and thus interact with each other better. The obtained high-conductivity and heat-resistant cable material for new energy vehicles can maintain high conductivity at high temperatures and reduce energy loss when transmitting electrical energy at high temperatures.
[0020] Preferably, in step 1), copper, bismuth trioxide, boron trioxide, tellurium oxide and antimony trioxide are first ground into particles with a particle size of ≤1 mm and then mixed.
[0021] By adopting the above technical scheme, copper, bismuth trioxide, boron trioxide, tellurium oxide and antimony trioxide are first ground into particles with a particle size of ≤1 mm, so that copper, bismuth trioxide, boron trioxide, tellurium oxide and antimony trioxide are mixed more evenly after melting, so as to better cooperate with each other, and the obtained high-conductivity and heat-resistant cable material for new energy vehicles can better maintain high conductivity at high temperatures.
[0022] Preferably, in step 2), air is firstly extracted until the pressure drops to 0.01-0.02 MPa, and then heated to 1130-1150°C.
[0023] By adopting the above technical solution, the air is extracted to remove oxygen, so that it is not easy to oxidize during the heating and melting process. The high-conductivity and heat-resistant cable material for new energy vehicles obtained is of better quality and can maintain high conductivity at high temperatures.
[0024] Preferably, in the step 2), after heating to 1130-1150° C., an inert gas is injected to increase the pressure to 1-2 MPa, and the temperature is maintained at 1-2 MPa.
[0025] By adopting the above technical solution, by injecting inert gas to increase the pressure to 1-2MPa, the metal structure can be better induced to change under high pressure, so that the high conductivity and heat-resistant cable material for new energy vehicles can have better conductivity at high temperatures.
[0026] Preferably, the inert gas is neon.
[0027] By adopting the above technical solution and specifically selecting neon as the inert gas, the effect of inducing metal structure changes in a high-pressure neon atmosphere is better, which can further improve the conductivity of high-conductivity and heat-resistant cable materials for new energy vehicles at high temperatures.
[0028] Preferably, in step 3), the cooling is carried out naturally at an ambient temperature of 25-30°C.
[0029] By adopting the above technical solution and cooling naturally at an ambient temperature of 25-30°C, damage to the metal structure caused by excessively rapid cooling can be avoided, and the high-conductivity and heat-resistant cable material for new energy vehicles obtained can be of better quality and better suitable for new energy vehicles.
[0030] In summary, this application has the following beneficial effects:
[0031] 1. Since the high-conductivity heat-resistant cable material for new energy vehicles prepared in this application by adding bismuth trioxide, boron trioxide, tellurium oxide and antimony trioxide into copper in a specific proportion has little resistance increase at high temperature, has good high temperature resistance, and can maintain high conductivity. At low temperatures, the conductivity is close to that of pure copper materials, and at high temperatures, the conductivity is better than that of pure copper materials. It is very suitable for use in new energy vehicles.
[0032] 2. In the present application, it is preferred to specifically select the mass ratio of copper, bismuth trioxide, boron trioxide, tellurium oxide, and antimony trioxide so that the high-conductivity and heat-resistant cable material for new energy vehicles has less resistance increase at high temperatures, better conductivity at high temperatures, better reduction of energy loss, and is more conducive to extending the battery life when used in new energy vehicles.
[0033] 3. In the present application, neon is preferably selected as the inert gas. Under the high-pressure neon atmosphere, the effect of inducing changes in the metal structure is better, which can further improve the conductivity of the high-conductivity and heat-resistant cable material for new energy vehicles at high temperatures. DETAILED DESCRIPTION
[0034] The present application is further described in detail below with reference to the embodiments.
[0035] Example 1
[0036] A high-conductivity and heat-resistant cable material for new energy vehicles, made of the following components:
[0037] Copper, bismuth trioxide, boron trioxide, tellurium oxide, antimony trioxide.
[0038] The preparation method of the high-conductivity and heat-resistant cable material for new energy vehicles comprises the following steps:
[0039] Step 1), 80kg of copper, 7kg of bismuth trioxide, 3kg of boron trioxide, 6kg of tellurium oxide, and 4kg of antimony trioxide are put into a grinding device and ground into particles with a particle size of ≤1mm, and then put into a stirring kettle, the speed is 120r / min, stirred for 20min, and mixed evenly to obtain a mixed material.
[0040] Step 2), the mixed material is put into a furnace, the air is evacuated until the pressure drops to 0.01 MPa, then heated to 1130°C, and then neon gas is injected to increase the pressure to 1 MPa, and the temperature is kept at 1130°C at 1 MPa for 60 minutes to obtain a composite metal liquid.
[0041] Step 3), injecting the composite metal liquid into the mold, and then placing the mold in a ventilated environment at 25°C, cooling naturally, and demolding to form a high-conductivity and heat-resistant cable material for new energy vehicles.
[0042] Copper was commercially available, CAS number: 7440-50-8.
[0043] Bismuth trioxide is commercially available, CAS number: 1304-76-3.
[0044] Boron trioxide is commercially available, CAS number: 1303-86-2.
[0045] Tellurium oxide is commercially available, CAS number: 7446-07-3.
[0046] Antimony trioxide is commercially available, CAS number: 1309-64-4.
[0047] Example 2
[0048] A high-conductivity and heat-resistant cable material for new energy vehicles, made of the following components:
[0049] Copper, bismuth trioxide, boron trioxide, tellurium oxide, antimony trioxide.
[0050] The preparation method of the high-conductivity and heat-resistant cable material for new energy vehicles comprises the following steps:
[0051] Step 1), 82kg of copper, 6.5kg of bismuth trioxide, 2.5kg of boron trioxide, 5.5kg of tellurium oxide, and 3.5kg of antimony trioxide are put into a grinding device and ground into particles with a particle size of ≤1mm, and then put into a stirring kettle at a speed of 135r / min, stirred for 25min, and mixed evenly to obtain a mixed material.
[0052] Step 2), the mixed material is put into a furnace, the air is evacuated until the pressure drops to 0.015MPa, then heated to 1140°C, and then neon is injected to increase the pressure to 1.5MPa, and the temperature is kept at 1140°C at 1.5MPa for 65min to obtain a composite metal liquid.
[0053] Step 3), injecting the composite metal liquid into the mold, and then placing the mold in a ventilated environment at 28°C, cooling naturally, and demolding to form a high-conductivity and heat-resistant cable material for new energy vehicles.
[0054] Copper was commercially available, CAS number: 7440-50-8.
[0055] Bismuth trioxide is commercially available, CAS number: 1304-76-3.
[0056] Boron trioxide is commercially available, CAS number: 1303-86-2.
[0057] Tellurium oxide is commercially available, CAS number: 7446-07-3.
[0058] Antimony trioxide is commercially available, CAS number: 1309-64-4.
[0059] Example 3
[0060] A high-conductivity and heat-resistant cable material for new energy vehicles, made of the following components:
[0061] Copper, bismuth trioxide, boron trioxide, tellurium oxide, antimony trioxide.
[0062] The preparation method of the high-conductivity and heat-resistant cable material for new energy vehicles comprises the following steps:
[0063] Step 1), 84kg of copper, 6kg of bismuth trioxide, 2kg of boron trioxide, 5kg of tellurium oxide, and 3kg of antimony trioxide are put into a grinding device and ground into particles with a particle size of ≤1mm, and then put into a stirring kettle, the speed is 150r / min, stirred for 30min, and mixed evenly to obtain a mixed material.
[0064] Step 2), the mixed material is put into a furnace, the air is evacuated until the pressure drops to 0.02MPa, then heated to 1150°C, and then neon is injected to increase the pressure to 2MPa, and the temperature is kept at 1150°C at 2MPa for 70min to obtain a composite metal liquid.
[0065] Step 3), injecting the composite metal liquid into the mold, and then placing the mold in a ventilated environment at 30°C, cooling naturally, and demolding to form a high-conductivity and heat-resistant cable material for new energy vehicles.
[0066] Copper was commercially available, CAS number: 7440-50-8.
[0067] Bismuth trioxide is commercially available, CAS number: 1304-76-3.
[0068] Boron trioxide is commercially available, CAS number: 1303-86-2.
[0069] Tellurium oxide is commercially available, CAS number: 7446-07-3.
[0070] Antimony trioxide is commercially available, CAS number: 1309-64-4.
[0071] Comparative Example 1
[0072] A high-conductivity and heat-resistant cable material for new energy vehicles, made of the following components:
[0073] Copper, zinc, boron trioxide, tellurium oxide, antimony trioxide.
[0074] The preparation method of the high-conductivity and heat-resistant cable material for new energy vehicles comprises the following steps:
[0075] Step 1), 82kg of copper, 6.5kg of zinc, 2.5kg of boron trioxide, 5.5kg of tellurium oxide, and 3.5kg of antimony trioxide are put into a grinding device and ground into particles with a particle size of ≤1mm, and then put into a stirring kettle, the speed is 135r / min, stirred for 25min, and mixed evenly to obtain a mixed material.
[0076] Step 2), the mixed material is put into a furnace, the air is evacuated until the pressure drops to 0.015MPa, then heated to 1140°C, and then neon is injected to increase the pressure to 1.5MPa, and the temperature is kept at 1140°C at 1.5MPa for 65min to obtain a composite metal liquid.
[0077] Step 3), injecting the composite metal liquid into the mold, and then placing the mold in a ventilated environment at 28°C, cooling naturally, and demolding to form a high-conductivity and heat-resistant cable material for new energy vehicles.
[0078] Copper was commercially available, CAS number: 7440-50-8.
[0079] Zinc was commercially available, CAS number: 7440-66-6.
[0080] Boron trioxide is commercially available, CAS number: 1303-86-2.
[0081] Tellurium oxide is commercially available, CAS number: 7446-07-3.
[0082] Antimony trioxide is commercially available, CAS number: 1309-64-4.
[0083] Comparative Example 2
[0084] A high-conductivity and heat-resistant cable material for new energy vehicles, made of the following components:
[0085] Copper, bismuth trioxide, tin, tellurium oxide, antimony trioxide.
[0086] The preparation method of the high-conductivity and heat-resistant cable material for new energy vehicles comprises the following steps:
[0087] Step 1), 82kg of copper, 6.5kg of bismuth trioxide, 2.5kg of tin, 5.5kg of tellurium oxide, and 3.5kg of antimony trioxide are put into a grinding device and ground into particles with a particle size of ≤1mm, and then put into a stirring kettle at a speed of 135r / min, stirred for 25min, and mixed evenly to obtain a mixed material.
[0088] Step 2), the mixed material is put into a furnace, the air is evacuated until the pressure drops to 0.015MPa, then heated to 1140°C, and then neon is injected to increase the pressure to 1.5MPa, and the temperature is kept at 1140°C at 1.5MPa for 65min to obtain a composite metal liquid.
[0089] Step 3), injecting the composite metal liquid into the mold, and then placing the mold in a ventilated environment at 28°C, cooling naturally, and demolding to form a high-conductivity and heat-resistant cable material for new energy vehicles.
[0090] Copper was commercially available, CAS number: 7440-50-8.
[0091] Bismuth trioxide is commercially available, CAS number: 1304-76-3.
[0092] Tin is commercially available, CAS number: 7440-31-5.
[0093] Tellurium oxide is commercially available, CAS number: 7446-07-3.
[0094] Antimony trioxide is commercially available, CAS number: 1309-64-4.
[0095] Comparative Example 3
[0096] A high-conductivity and heat-resistant cable material for new energy vehicles, made of the following components:
[0097] Copper, bismuth trioxide, boron trioxide, magnesium, antimony trioxide.
[0098] The preparation method of the high-conductivity and heat-resistant cable material for new energy vehicles comprises the following steps:
[0099] Step 1), 82kg of copper, 6.5kg of bismuth trioxide, 2.5kg of boron trioxide, 5.5kg of magnesium, and 3.5kg of antimony trioxide are put into a grinding device and ground into particles with a particle size of ≤1mm, and then put into a stirring kettle, the speed is 135r / min, stirred for 25min, and mixed evenly to obtain a mixed material.
[0100] Step 2), the mixed material is put into a furnace, the air is evacuated until the pressure drops to 0.015MPa, then heated to 1140°C, and then neon is injected to increase the pressure to 1.5MPa, and the temperature is kept at 1140°C at 1.5MPa for 65min to obtain a composite metal liquid.
[0101] Step 3), injecting the composite metal liquid into the mold, and then placing the mold in a ventilated environment at 28°C, cooling naturally, and demolding to form a high-conductivity and heat-resistant cable material for new energy vehicles.
[0102] Copper was commercially available, CAS number: 7440-50-8.
[0103] Bismuth trioxide is commercially available, CAS number: 1304-76-3.
[0104] Boron trioxide is commercially available, CAS number: 1303-86-2.
[0105] Magnesium was commercially available, CAS number: 7439-95-4.
[0106] Antimony trioxide is commercially available, CAS number: 1309-64-4.
[0107] Comparative Example 4
[0108] A high-conductivity and heat-resistant cable material for new energy vehicles, made of the following components:
[0109] Copper, bismuth trioxide, boron trioxide, tellurium oxide, aluminum.
[0110] The preparation method of the high-conductivity and heat-resistant cable material for new energy vehicles comprises the following steps:
[0111] Step 1), 82kg of copper, 6.5kg of bismuth trioxide, 2.5kg of boron trioxide, 5.5kg of tellurium oxide, and 3.5kg of aluminum are put into a grinding device and ground into particles with a particle size of ≤1mm, and then put into a stirring kettle at a speed of 135r / min, stirred for 25min, and mixed evenly to obtain a mixed material.
[0112] Step 2), the mixed material is put into a furnace, the air is evacuated until the pressure drops to 0.015MPa, then heated to 1140°C, and then neon is injected to increase the pressure to 1.5MPa, and the temperature is kept at 1140°C at 1.5MPa for 65min to obtain a composite metal liquid.
[0113] Step 3), injecting the composite metal liquid into the mold, and then placing the mold in a ventilated environment at 28°C, cooling naturally, and demolding to form a high-conductivity and heat-resistant cable material for new energy vehicles.
[0114] Copper was commercially available, CAS number: 7440-50-8.
[0115] Bismuth trioxide is commercially available, CAS number: 1304-76-3.
[0116] Boron trioxide is commercially available, CAS number: 1303-86-2.
[0117] Tellurium oxide is commercially available, CAS number: 7446-07-3.
[0118] Aluminum was commercially available, CAS number: 7429-90-5.
[0119] Comparative Example 5
[0120] A high-conductivity and heat-resistant cable material for new energy vehicles, made of the following components:
[0121] Copper, zinc, tin, magnesium, aluminum.
[0122] The preparation method of the high-conductivity and heat-resistant cable material for new energy vehicles comprises the following steps:
[0123] Step 1), 82kg copper, 6.5kg zinc, 2.5kg tin, 5.5kg magnesium and 3.5kg aluminum are put into a grinding device and ground into particles with a particle size of ≤1mm, and then put into a stirring kettle, rotate at a speed of 135r / min, stir for 25min, mix evenly, and obtain a mixed material.
[0124] Step 2), the mixed material is put into a furnace, the air is evacuated until the pressure drops to 0.015MPa, then heated to 1140°C, and then neon is injected to increase the pressure to 1.5MPa, and the temperature is kept at 1140°C at 1.5MPa for 65min to obtain a composite metal liquid.
[0125] Step 3), injecting the composite metal liquid into the mold, and then placing the mold in a ventilated environment at 28°C, cooling naturally, and demolding to form a high-conductivity and heat-resistant cable material for new energy vehicles.
[0126] Copper was commercially available, CAS number: 7440-50-8.
[0127] Zinc was commercially available, CAS number: 7440-66-6.
[0128] Tin is commercially available, CAS number: 7440-31-5.
[0129] Magnesium was commercially available, CAS number: 7439-95-4.
[0130] Aluminum was commercially available, CAS number: 7429-90-5.
[0131] Comparative Example 6
[0132] A high-conductivity and heat-resistant cable material for new energy vehicles, made of pure copper.
[0133] Pure copper was purchased from Jinan Ruijin Trading Co., Ltd., with a copper content of 99.98%.
[0134] Comparative Example 7
[0135] A high-conductivity and heat-resistant cable material for new energy vehicles, made of the following components:
[0136] Copper, bismuth trioxide, boron trioxide, tellurium oxide, antimony trioxide.
[0137] The preparation method of the high-conductivity and heat-resistant cable material for new energy vehicles comprises the following steps:
[0138] Step 1), 82kg of copper, 6.5kg of bismuth trioxide, 2.5kg of boron trioxide, 5.5kg of tellurium oxide, and 3.5kg of antimony trioxide are put into a grinding device and ground into particles with a particle size of ≤1mm, and then put into a stirring kettle at a speed of 135r / min, stirred for 25min, and mixed evenly to obtain a mixed material.
[0139] Step 2), put the mixed material into the furnace, evacuate the air until the pressure drops to 0.015MPa, then heat to 1140°C, then inject nitrogen to increase the pressure to 1.5MPa, maintain a constant temperature of 1140°C at 1.5MPa for 65min to obtain a composite metal liquid.
[0140] Step 3), injecting the composite metal liquid into the mold, and then placing the mold in a ventilated environment at 28°C, cooling naturally, and demolding to form a high-conductivity and heat-resistant cable material for new energy vehicles.
[0141] Copper was commercially available, CAS number: 7440-50-8.
[0142] Bismuth trioxide is commercially available, CAS number: 1304-76-3.
[0143] Boron trioxide is commercially available, CAS number: 1303-86-2.
[0144] Tellurium oxide is commercially available, CAS number: 7446-07-3.
[0145] Antimony trioxide is commercially available, CAS number: 1309-64-4.
[0146] Comparative Example 8
[0147] A high-conductivity and heat-resistant cable material for new energy vehicles, made of the following components:
[0148] Copper, bismuth trioxide, boron trioxide, tellurium oxide, antimony trioxide.
[0149] The preparation method of the high-conductivity and heat-resistant cable material for new energy vehicles comprises the following steps:
[0150] Step 1), 82kg of copper, 6.5kg of bismuth trioxide, 2.5kg of boron trioxide, 5.5kg of tellurium oxide, and 3.5kg of antimony trioxide are put into a grinding device and ground into particles with a particle size of ≤1mm, and then put into a stirring kettle at a speed of 135r / min, stirred for 25min, and mixed evenly to obtain a mixed material.
[0151] Step 2), putting the mixed material into a furnace, evacuating the air until the pressure drops to 0.015 MPa, and then heating to 1140° C., maintaining a constant temperature of 1140° C. for 65 minutes to obtain a composite metal liquid.
[0152] Step 3), injecting the composite metal liquid into the mold, and then placing the mold in a ventilated environment at 28°C, cooling naturally, and demolding to form a high-conductivity and heat-resistant cable material for new energy vehicles.
[0153] Copper was commercially available, CAS number: 7440-50-8.
[0154] Bismuth trioxide is commercially available, CAS number: 1304-76-3.
[0155] Boron trioxide is commercially available, CAS number: 1303-86-2.
[0156] Tellurium oxide is commercially available, CAS number: 7446-07-3.
[0157] Antimony trioxide is commercially available, CAS number: 1309-64-4.
[0158] Experiment 1
[0159] The high-conductivity and heat-resistant cable materials for new energy vehicles of various embodiments and comparative examples are used to make a 1mm cross-section 2 , the length of the tested wire is 1m, and the resistance of the tested wire is tested by a multimeter at 20℃ and 100℃ respectively, and the resistivity is calculated.
[0160] The multimeter was purchased from Gaomei Instrument (Tianjin) Technology Co., Ltd., model METRAport3A.
[0161] In each embodiment or comparative example, 10 wires to be tested were manufactured, and the test data were averaged.
[0162] The specific test data of Experiment 1 are shown in Table 1.
[0163] Table 1
[0164] 20℃ resistivity (Ω·m) 100℃ resistivity (Ω·m) Example 1 <![CDATA[1.796×10 -8 ]]> <![CDATA[1.835×10 -8 ]]> Example 2 <![CDATA[1.794×10 -8 ]]> <![CDATA[1.831×10 -8 ]]> Example 3 <![CDATA[1.798×10 -8 ]]> <![CDATA[1.838×10 -8 ]]> Comparative Example 1 <![CDATA[1.826×10 -8 ]]> <![CDATA[2.088×10 -8 ]]> Comparative Example 2 <![CDATA[1.819×10 -8 ]]> <![CDATA[2.083×10 -8 ]]> Comparative Example 3 <![CDATA[1.831×10 -8 ]]> <![CDATA[2.092×10 -8 ]]> Comparative Example 4 <![CDATA[1.822×10 -8 ]]> <![CDATA[2.086×10 -8 ]]> Comparative Example 5 <![CDATA[1.835×10 -8 ]]> <![CDATA[2.096×10 -8 ]]> Comparative Example 6 <![CDATA[1.783×10 -8 ]]> <![CDATA[2.064×10 -8 ]]> Comparative Example 7 <![CDATA[1.802×10 -8 ]]> <![CDATA[1.906×10 -8 <!-- 7 -->]]> Comparative Example 8 <![CDATA[1.806×10 -8 ]]> <![CDATA[1.917×10 -8 ]]>
[0165] According to the data comparison between the embodiments and the comparative examples in Table 1, the resistivity of the high-conductivity and heat-resistant cable materials for new energy vehicles prepared in the embodiments at 20°C is similar to that of comparative example 6, that is, the resistivity of the high-conductivity and heat-resistant cable materials for new energy vehicles prepared in the embodiments at 20°C is similar to the resistivity of pure copper, and the resistivity of the high-conductivity and heat-resistant cable materials for new energy vehicles prepared in the embodiments at 100°C is significantly lower than that of comparative example 6, that is, the resistivity of the high-conductivity and heat-resistant cable materials for new energy vehicles prepared in the embodiments at 100°C is significantly lower than that of pure copper. It can be seen that when a specific proportion of bismuth trioxide, boron trioxide, tellurium oxide, and antimony trioxide are added to copper, the obtained alloy material has high conductivity and can well retain high conductivity at high temperatures, and is very suitable for application in new energy vehicle cables.
[0166] Comparative Examples 1-5 use conventional copper alloy materials to replace one or more of bismuth trioxide, boron trioxide, tellurium oxide, and antimony trioxide. The resistivity of the obtained cable materials is higher than that of Comparative Example 6 at both 20°C and 100°C. It can be seen that only when bismuth trioxide, boron trioxide, tellurium oxide, and antimony trioxide are added to copper in a specific proportion can the electrical conductivity at high temperatures be greatly improved.
[0167] Comparative Example 7 uses nitrogen to replace neon gas, and Comparative Example 8 cancels the inert gas pressurization. The resistivity of the obtained cable material is higher than that of the embodiment at both 20°C and 100°C. It can be seen that the high-pressure neon atmosphere can better induce changes in the metal structure, making the low-temperature and high-temperature resistivity of the high-conductivity and heat-resistant cable material for new energy vehicles lower and the quality better.
[0168] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-conductivity and heat-resistant cable material for new energy vehicles. Features: Made from the following components in parts by weight: Copper 80-84 parts; 6-7 parts of bismuth trioxide; Boron trioxide 2-3 parts; Tellurium oxide 5-6 parts; 3-4 parts of antimony trioxide; The preparation method of the high-conductivity and heat-resistant cable material for new energy vehicles comprises the following steps: Step 1), copper, bismuth trioxide, boron trioxide, tellurium oxide, and antimony trioxide are uniformly mixed to obtain a mixed material; Step 2), heating the mixed material to 1130-1150°C, maintaining the temperature at 1130-1150°C for 60-70 minutes, and obtaining a composite metal liquid; Step 3), injecting the composite metal liquid into the mold and cooling it to form a high-conductivity and heat-resistant cable material for new energy vehicles; In the step 2), air is firstly extracted until the pressure drops to 0.01-0.02 MPa, and then heated to 1130-1150° C.; In the step 2), after heating to 1130-1150° C., an inert gas is injected to increase the pressure to 1-2 MPa, and the temperature is maintained at 1-2 MPa.
2. A high-conductivity and heat-resistant cable material for new energy vehicles according to claim 1, Features: The mass ratio of copper, bismuth trioxide, boron trioxide, tellurium oxide and antimony trioxide is 82: 6.5:2.5:5.5:3.5。 3. A high-conductivity and heat-resistant cable material for new energy vehicles according to claim 1, Features: In the step 1), copper, bismuth trioxide, boron trioxide, tellurium oxide and antimony trioxide are firstly ground into particles with a particle size of ≤1 mm, and then mixed.
4. A high-conductivity and heat-resistant cable material for new energy vehicles according to claim 1, Features: The inert gas is neon.
5. A high-conductivity and heat-resistant cable material for new energy vehicles according to claim 1, Features: In the step 3), during cooling, the mixture is cooled naturally at an ambient temperature of 25-30°C.
